2014
DOI: 10.3791/51222
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput Screening for Broad-spectrum Chemical Inhibitors of RNA Viruses

Abstract: RNA viruses are responsible for major human diseases such as flu, bronchitis, dengue, Hepatitis C or measles. They also represent an emerging threat because of increased worldwide exchanges and human populations penetrating more and more natural ecosystems. A good example of such an emerging situation is chikungunya virus epidemics of [2005][2006] in the Indian Ocean. Recent progresses in our understanding of cellular pathways controlling viral replication suggest that compounds targeting host cell functions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
1
12
0
1
Order By: Relevance
“…An alternative hypothesis would be differential capacity of the cell types to develop a protective antiviral response. The innate immune response, a major component of the antiviral response, has indeed been proven to be critically important in restricting infection by neurotropic viruses [57][58][59] and in determining TBEV tropism in different brain areas in murine models [49,60]. Also, studies using rodent models have shown that distinct brain cell types develop different antiviral states.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative hypothesis would be differential capacity of the cell types to develop a protective antiviral response. The innate immune response, a major component of the antiviral response, has indeed been proven to be critically important in restricting infection by neurotropic viruses [57][58][59] and in determining TBEV tropism in different brain areas in murine models [49,60]. Also, studies using rodent models have shown that distinct brain cell types develop different antiviral states.…”
Section: Discussionmentioning
confidence: 99%
“…[ 84 ] Plates with Z’-values below 0.5 were discarded. The inhibition of ATPase activity was calculated as follow: [ 85 ] Selected hits were further tested with kinetic assays. Results were reported as ATPase reaction velocities.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, these results are probably an illustration of the interest of designing whole cell/phenotypic assays of sufficient sensitivity (a bioluminescent virus in the present case). 12 This led us to detect an unexpected biological effect and provided a simple biological mean not only to undertake further structure–activity study but also to find the mode of action of this series of compounds.…”
Section: Discussionmentioning
confidence: 99%
“…As explained in more detail in our previous report, 1 in the course of a screening campaign of new chemical entities 2 11 against infectious agents, compounds 1 and 2 were found active on our whole cell measles virus replication assay (Figure 1 ). 12 An initial structure–activity study led to confirmation of the potential of this original chemotype and to greatly improved antiviral compounds, including the 2-(3-isopropyloxy-1 H -pyrazol-1-yl)pyrimidine derivative 3 , which displayed a subnanomolar MIC 50 on this measles virus replication assay (Figure 1 ). Moreover, a search for the biochemical mechanism of action of this series pointed out that, as for other recently reported compounds, 13 18 the inhibition of the cellular dihydroorotate dehydrogenase (DHODH) is at the origin of the antiviral effect.…”
Section: Introductionmentioning
confidence: 97%